ACTIVITY TESTS OF ANTIBACTERIAL CREAM OF BAY LEAF (Syzygium polyanthum) ETHANOL EXTRACT AGAINST BACTERIA Propionibacterium acnes - Octora, Debi Dinha; Sari, Delima (Jurnal FARMASIMED (JFM), 2023)
Bay leaf (Syzygium polyanthum) is a plant that is widely used as a flavor enhancer. Based on research that has been done, bay leaves contain flavonoids, alkaloids, tannins, and saponins that have the ability to act as natural antibacterial agents. Improper use of antibiotics in the treatment of infections can cause resistance, so it is necessary to use antibiotics from natural ingredients that have an optimal working power and are relatively safe. P. acnes is one type of bacteria that can cause acne. The purpose of this research is to find out the effective antibacterial activity of bay leaf ethanol extract cream preparation against P. acnes bacteria. This research is an experimental research with 3 different concentration variations. The research results show that there is antibacterial activity at each concentration with an average diameter of the clear zone of 10.06 mm, 14.4 mm and 20.16 mm, the higher the concentration of EEDS, the higher the inhibitory power against P. acnes bacteria growth. The conclusion of the activity of salam leaves with a concentration of 5%, 10%, and 15% provides the most effective inhibition of bacterial growth with a concentration of 10%, 15% which is included in the strong category. Suggestions are expected to the next researcher to be able to test other bacteria and make a greater concentration than the previous research from EEDS.